2001
DOI: 10.1111/j.1349-7006.2001.tb01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Induction of Tumor‐specific Cytotoxic T Lymphocytes from Patients with Non‐small Cell Lung Cancer Using CD80‐transfected Autologous Tumor Cells

Abstract: Cytotoxic T lymphocytes (CTL) against human lung cancer cells are difficult to induce by a conventional method using tumor cell stimulation probably due to an insufficiency of tumor antigens (TA) or costimulatory molecules such as CD80. We, therefore, investigated the potential of CD80-transfected tumor cells as stimulators of the in vitro induction of autologous tumor-specific CTL from regional lymph node lymphocytes in patients with lung cancer. Five non-small cell lung cancer cell lines (two adenocarcinomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…Many strategies in cancer immunotherapy have aimed to trigger anti-tumor immune responses by an MHC class I-restricted tumor-specific CTL response (Takenoyama et al, 2001;Kass et al, 2003). However, to generate efficiently CD8+ T effector and memory cells, CD4+ T helper (Th) cells are essentially required (Baxevanis et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies in cancer immunotherapy have aimed to trigger anti-tumor immune responses by an MHC class I-restricted tumor-specific CTL response (Takenoyama et al, 2001;Kass et al, 2003). However, to generate efficiently CD8+ T effector and memory cells, CD4+ T helper (Th) cells are essentially required (Baxevanis et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…One part was sent for a pathologic examination, and the other part was prepared for single cell suspension and was frozen at Ϫ 130°C until use, as described previously. 30 A pathologic examination revealed that the patient's hilar lymph nodes were involved with carcinoma cells; therefore, the it is possible that the RLNLs in this study may have contained lung carcinoma cells. The frozen RLNLs were thawed rapidly, and 3.6 ϫ 10 6 cells were divided into 3 wells of a 24-well plate (1.2 ϫ 10 6 cells per well) (Iwaki Glass).…”
Section: Induction Of Bulk Ctls and Generation Of Ctl Clonesmentioning
confidence: 99%
“…30 A stable transfection of CD80 molecules was confirmed by flow cytometry after staining with FITC-conjugated anti-human CD80 (Pharmingen, San Diego, CA).…”
Section: Transfection Of Human Cd80 Into G603l Cellsmentioning
confidence: 99%
“…Each lymph node was divided into two parts; one for the histological diagnosis and one for this study. Lymphocytes from each lymph node were mixed and stored at -80˚C until use, as described previously (17). They were then rapidly thawed and stimulated with an irradiated (100 Gy) CD80-transfected autologous tumor cell line (F1121L and L1023L) weekly at a tumor-to-lymphocyte ratio of 1:10 in culture medium as described previously (17).…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocytes from each lymph node were mixed and stored at -80˚C until use, as described previously (17). They were then rapidly thawed and stimulated with an irradiated (100 Gy) CD80-transfected autologous tumor cell line (F1121L and L1023L) weekly at a tumor-to-lymphocyte ratio of 1:10 in culture medium as described previously (17). The tumor-specific induction of CTLs was considered to be successful if the CTLs lysed more than 10% of the autologous tumor cells at an effector/target ratio of 30/1 and did not lyse autologous Epstein-Barr virus-transformed B cells during the 4-h standard 51Cr release assay performed on day 28 of the mixed lymphocyte-tumor cell culture (MLTC).…”
Section: Introductionmentioning
confidence: 99%